The Analysis of E-Government Services Adoption and Use in Slovenian Information Society between 2014 and 2017 - Mitja Dečman (Central European Public Administration Review)
With the increasing role of information and communication technology (ICT) in the society, ICT’s role is gaining importance in the aspect of provision and use of the public sector services for the citizens. Especially in the European Union different activities have been conducted through the years to promote ICT use in the society. It has been mainly based on the Digital Agenda for Europe (DAE), which underlines the key role of ICT in the efforts to achieve its strategic objectives. Slovenia as an EU member state follows these directions but positions itself among less successful states in the EU. The well-known European Digital Economy and Society Index ranks Slovenia to the lower half of member states indicating possibilities for improvement. Although much can be said and done about the service-providers side this paper focuses on the users’ side and especially on their digital inequality. The lack of studies in the area of digital inequality and online government services adoption and use is the main motivation for this research. The research uses the data provided by Slovenian annual survey Use of Information and Communication Technology in Households and by Individuals of the last four years. The analysis of this data, presented in the paper, exhibits that changes for the better are detected in Slovenian society, but the situation in public-sector services is not optima. The results demonstrate the existence of digital inequality considering the income level of households and education level of individual users. The synthesis of the data demonstrates that the Slovenian government and its ministries should consider adding tangible actions to the already set strategies if the country wants to catch up with the leading countries of the EU and achieve goals, set by the DAE.